Complete mitogenomes for two lineages of the Australian smelt, Retropinna semoni (Osmeriformes: Retropinnidae). Issue 1 (1st January 2016) - Schmidt, Daniel J.; Islam, Md. Rakeb-Ul; Hughes, Jane M.
Abstract: Complete mitochondrial genome sequences were determined for two lineages ("CEQ" and "SEQ") of the Australian smelt, Retropinna semoni . Both mitogenomes contain the typical vertebrate arrangement of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes and control region. A conventional start codon for ND2 was not present in either lineage; instead CTG (Leucine) was present at this position. These sequences will be a useful resource for evolutionary studies of a significant species complex in the Australian freshwater fish fauna.